2015
DOI: 10.1016/j.actbio.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Young’s modulus on the neuronal differentiation of mouse embryonic stem cells

Abstract: There is substantial evidence that cells produce a diverse response to changes in ECM stiffness depending on their identity. Our aim was to understand how stiffness impacts neuronal differentiation of embryonic stem cells (ESC's), and how this varies at three specific stages of the differentiation process. In this investigation, three effects of stiffness on cells were considered; attachment, expansion and phenotypic changes during differentiation. Stiffness was varied from 2 kPa to 18 kPa to finally 35 kPa. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 94 publications
5
54
0
Order By: Relevance
“…Our results indicate that nuclear rotation is dependent on substrate elasticity. Our results on hard substrates are coherent with previous studies; however, we showed for the first time that a significant reduction in the prevalence, magnitude, and speed of rotation occur on soft substrates designed to mimic the physical properties of resting muscle tissue (Al-Rekabi and Pelling, 2013; Ali et al, 2015;Collinsworth et al, 2002;Mathur et al, 2001;Nyland and Maughan, 2000;Ogneva, 2010). Previous studies on nuclear rotation have been performed on hard substrates that can have a stiffness in the GPa range (Brosig et al, 2010;Ji et al, 2007;Levy and Holzbaur, 2008;Albrecht-Buehler, 1986b, 1988;Wilson and Holzbaur, 2012;Yao and Ellingson, 1969).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that nuclear rotation is dependent on substrate elasticity. Our results on hard substrates are coherent with previous studies; however, we showed for the first time that a significant reduction in the prevalence, magnitude, and speed of rotation occur on soft substrates designed to mimic the physical properties of resting muscle tissue (Al-Rekabi and Pelling, 2013; Ali et al, 2015;Collinsworth et al, 2002;Mathur et al, 2001;Nyland and Maughan, 2000;Ogneva, 2010). Previous studies on nuclear rotation have been performed on hard substrates that can have a stiffness in the GPa range (Brosig et al, 2010;Ji et al, 2007;Levy and Holzbaur, 2008;Albrecht-Buehler, 1986b, 1988;Wilson and Holzbaur, 2012;Yao and Ellingson, 1969).…”
Section: Discussionsupporting
confidence: 92%
“…Traditionally, mammalian cells have been cultured on hard glass or plastic substrates. Here, we created “soft” substrates by coating them with a thick GE cross‐linked with glutaraldehyde (GA) gel (GXG gel), as described previously (Al‐Rekabi and Pelling, ; Ali, Wall, Mason, Pelling, & Veraitch, ). The GXG gel stiffness was tuned to be within the resting muscle tissue stiffness regime (Collinsworth et al, ; Mathur et al, ; Nyland and Maughan, ; Ogneva, ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of the matrix are known to affect the cellular behavior and differentiation of many cell types . However, conflicting reports exist in the literature regarding the sensitivity of pluripotent and neural stem cells during neural differentiation to changes in the Young's Modulus of the culture substrate . It has been suggested that both the lineage and maturation state of the cells play a role in the mechanosensitivity of neural cell types, but the transmittance of mechanical signals to neural cells is complex and not yet fully understood, as multiple pathways play a role .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the β‐III tubulin mRNA level reached a 3.2‐fold increase roughly on all hydrogels after 1 day of culture. However, several investigations reported the β‐III tubulin upregulation in other cell types after a longer culture period on the same substrate elasticity (Ali, Wall, Mason, Pelling, & Veraitch, ; Banerjee et al, ; Saha et al, ). In the next part of our study, the gene expression analysis of our panel of growth factors showed that most of them could be modulated by substrate stiffness.…”
Section: Discussionmentioning
confidence: 99%